The AhR pathway regulation in phthalates-induced cancer promotion, progression and metastasis: a scoping review - Mostafa Akbariani; Mahmoud Omidi; Zohreh Shahabi; Hamed Haghi-Aminjan; Amir Shadboorestan (Cancer Cell International)
Abstract Background Cancer remains a leading cause of death worldwide. Environmental factors, specifically endocrine-disrupting chemicals (EDCs), like phthalates, are increasingly being linked to cancer development. Phthalates, widely used in consumer products, can activate the aryl hydrocarbon receptor (AhR). This scoping review investigates how phthalate exposure influences cancer-related molecular pathways through the regulation of the AhR pathway to uncover the underlying mechanisms. Methods We conducted a comprehensive literature search in PubMed, Scopus, and Web of Science (ISI) database up to November 2023. Studies were selected based on peer-reviewed status, focus on phthalates’ effects on cancer through the AhR pathway and the availability of full texts. Data extraction emphasized study models, types of phthalates, exposure protocols, and cancer-related signaling pathway outcomes. Results Out of 108 initial articles, 10 met the inclusion criteria. Di-(2-ethylhexyl) phthalate (DEHP) and its metabolite Mono (2-ethylhexyl) phthalate (MEHP) were found to promote cancer cell proliferation, epithelial-mesenchymal transition (EMT), and chemoresistance through the AhR pathway. Specifically, DEHP activated AhR, leading to elevated expression of EMT markers, increased cancer stem cell populations, and enhanced drug metabolism and resistance. Other phthalates, such as Butyl Benzyl Phthalate (BBP), also activated AhR-mediated pathways, promoting angiogenesis and metastasis. Conclusion Phthalates activate the AhR pathway, contributing to cancer progression underscoring the need for developing effective interventions against phthalate-induced carcinogenesis. Regulatory measures to minimize phthalate exposure are crucial to preventing harmful health effects and improving cancer treatment outcomes.